Monitoring of Older Adult’s Joint Pain Management by Families Based on Information Technology (IT) Platform - Rizkiyani Istifada; Iswati Iswati; Wahyu Dini Candra Susila; Dwi Yuniar Ramadhani; Muh Asnoer Laagu (Adi Husada Nursing Journal, 2023)
Older adults experience an aging process that impacts a decrease in physiological function. Joint pain is one of the negative consequences of decreased physiological function. Older adults need a continuum of care to deal with the perceived vulnerability due to the effects of pain. The family has a role in self-management at home, but sometimes families experience difficulties in the mentoring process because of their high productivity outside the home. The research aims to explain monitoring on the pain scale, knowledge, skills, self-efficacy of older adults, and the level of family independence based on Information Technology (IT) platform. The method used is a case report on an older adult and the family for two months of monitoring. The intervention consisted of 4 meetings using psychoeducational techniques, cognitive restructuring, demonstration, and problem-solving. The result showed a decrease in the pain scale and an increase in the knowledge, skills, and self-efficacy of older adults. In addition, the result showed increased family independence after intervention. The family has an essential role in accompanying older adults during the joint pain management process. This result is expected to be a recommendation for health workers to maximize the part of the family in treating pain management in older adults.